New species and a record of myrmecophilous mites of the families Neopygmephoridae and Microdispidae (Acari: Heterostigmatina: Pygmephoroidea) associated with Lasius umbratus (Hymenoptera: Formicidae) from Western Siberia, Russia - Khaustov, Alexander A. (Zootaxa, 2016)
Two new myrmecophilous species of the family Neopygmephoridae (Acari: Pygmephoroidea), Petalomium brevicaudus sp. nov. and P. kurganiensis sp. nov. are described from the ant Lasius umbratus Nylander (Hymenoptera: Formicidae: Formicinae) in Western Siberia, Russia. Another myrmecophilous species of the family Microdispidae (Acari: Pygmephoroidea), Caesarodispus brevipes Mahunka, 1981, was also collected from the ant L. umbratus in Western Siberia, Russia. It is recorded from Russia for the first time and is redescribed in the present paper.